MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN IPA MATERI SIFAT-SIFAT BUNYI MENGGUNAKAN MODEL COOPERATIVE LEARNING - Gumiwang, Ridyo Estu; Suciana, Dola (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
The background to the problem in this research is the low learning outcomes of students in understanding the material on the properties of sound, with traditional learning making students disinterested and less active in learning. The aim of this research is to describe the improvement in student learning outcomes in science lessons on the properties of sound using the Cooperative Learning Model in class 2 of SDN Ngepoh. This research method is classroom action research (PTK) with class 2 research subjects as many as 12 students with 2 research cycles. The findings from this research are that the increase in student learning outcomes in science learning material on the properties of sound using the cooperative learning model starting from the Pre-cycle and then Cycle I to Cycle II shows an increase, which can be seen from the average in the Pre-cycle of 53, in Cycle I was 68.3 and in Cycle II it was 85. From these data it can be concluded that the use of the cooperative learning model in science learning can improve student learning outcomes. So, the cooperative learning model is effective in improving student learning outcomes in science lessons, especially material on the properties of sound.